The impact of learning motivation on mathematics anxiety among 4th grade elementary school students in Indonesia - Fadhilah, Miming; Riyadi , Riyadi; Kurniawan, Sandra Bayu (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Affective factors such as math anxiety have become a global concern in elementary education, as they have the potential to hinder students' cognitive development and engagement in mathematics learning. In the context of public elementary schools in a semi-urban area of Sragen Regency, this study aimed to analyze the effect of learning motivation on mathematics anxiety in fourth-grade students. This study used a quantitative approach with a quasi-experimental pretest–posttest control group design, focusing on the comparison between the intervention group and the control group. A total of 95 students were selected through cluster random sampling. Data were collected using a learning motivation questionnaire based on Self-Determination Theory and a validated mathematics anxiety scale. The analysis showed that increasing learning motivation significantly reduced levels of mathematics anxiety. Moreover, linear regression indicated a strong negative relationship between the two variables, with learning motivation explaining most of the variance in anxiety. These findings confirm that strengthening intrinsic motivation plays a significant role in reducing students' emotional distress towards mathematics. Therefore, motivation-based pedagogical strategies are recommended as an effective approach to creating a more positive and adaptive learning experience in elementary schools.